CIPP, Stake Model, Goal Free Model, Formative-Sumative Model (Apllications in Education) - Noor, Ahmad SUGIAN; Hermina, Dina; Mof, Yahya (RADINKA JAYA UTAMA PUBLISHER, 2025)
Program evaluation is a crucial component in efforts to improve educational quality. This article examines four primary evaluation frameworks CIPP (Context–Input–Process–Product), the Stake Model (Antecedents, Transactions, Outcomes), Goal Free Evaluation, and the Formative–Summative Model and illustrates their practical applications in the field. The CIPP model provides a comprehensive evaluation guide from needs analysis through outcome measurement, supporting ongoing decision‑making. The Stake Model emphasizes both descriptive and judgmental activities across initial conditions, instructional processes, and final outcomes, offering a complete picture of program effectiveness. Goal Free Evaluation adopts a fresh perspective by observing all real impacts including unanticipated effects without being bound by formal goal statements, thereby uncovering opportunities for innovative improvements. In contrast, the Formative–Summative Model divides evaluation into formative feedback during the process and summative assessment at the end, enabling timely interventions and comprehensive outcome measurement. By understanding the characteristics and advantages of each model, educators can select or combine the most appropriate frameworks to create adaptive, responsive, and sustainable learning.